Physical activity as a prognostic factor of pain intensity and disability in patients with low back pain: A systematic review - Oliveira, Crystian B. [UNESP]; Pinheiro, Marina B.; Teixeira, Renan J. [UNESP]; Franco, Márcia R.; Silva, Fernanda G. [UNESP]; Hisamatsu, Thalysi M. [UNESP]; Ferreira, Paulo H.; Pinto, Rafael Z. (Wiley, 2019)
Background and objective: Identifying factors that influence the course of low back pain (LBP) is important to help clinicians to identify those patients at higher risk of non-recovery. The objective of this systematic review was to investigate the prognostic role of physical activity in the course of LBP. Databases and data treatment: Literature searches were conducted in five electronic databases from their inception to February 2018. Prospective cohort studies investigating the influence of any type of physical activity in people with LBP were considered eligible. The primary outcomes were pain intensity and disability. Two independent reviewers extracted the data and assessed the methodological quality of the included studies. Results were stratified according to participants’ symptoms duration at baseline. Results: Twelve studies were considered eligible for this review. Of these, six included patients with chronic LBP, four studies did not specify the patients’ duration of symptoms, one study included patients with acute LBP, and one study included patients with subacute LBP. Included studies were heterogeneous in terms of physical activity assessment, outcomes, follow-up duration, and statistical methods, therefore, pooling of results was not performed. We found limited evidence to support the prognostic role of physical activity in the course of LBP. Conclusions: Our review identified limited evidence supporting physical activity as a prognostic factor in LBP. Future cohort studies are needed to clarify the strength and importance of this association. Significance: Despite recent research in the area, this systematic review shows that there is low quality evidence that physical activity may not be a prognostic factor for predicting pain and disability in patients with LBP.